Activities of the Catholic Church in the International Arena: Position of Pope Benedict XVI - Ivan Danyliuk (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія, 2018)
The article analyzes the diplomatic activity of the Catholic Church on the internationalarena in the views of Pope Benedict XVI.